2010
DOI: 10.1111/j.1600-0765.2010.01314.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between periodontal disease, physical activity and healthy diet among adults in Jordan

Abstract: A low physical activity level and a poor diet were significantly associated with increased odds of periodontal disease. Further studies are needed to understand this relationship in greater detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
114
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 44 publications
(50 reference statements)
6
114
0
4
Order By: Relevance
“…[93] Another previous author used the healthy eating index as a dietary quality assessment tool and found that a poor diet was linked with increased odds of periodontаl disease and the healthy diet may be associated with lower risk of periodontal disease. [109] This point of view was in agreement with Clapp & Little (1995) who found that women who continued their workout regimen throughout pregnancy compared to those who stopped their workout either before conception or in early pregnancy had а significantly (p < 0.05). [110] There is an association between high physical activity and low level of inflammatory markers, such C-reactive protein (CRP) and fibrinogen.…”
Section: Discussionsupporting
confidence: 85%
“…[93] Another previous author used the healthy eating index as a dietary quality assessment tool and found that a poor diet was linked with increased odds of periodontаl disease and the healthy diet may be associated with lower risk of periodontal disease. [109] This point of view was in agreement with Clapp & Little (1995) who found that women who continued their workout regimen throughout pregnancy compared to those who stopped their workout either before conception or in early pregnancy had а significantly (p < 0.05). [110] There is an association between high physical activity and low level of inflammatory markers, such C-reactive protein (CRP) and fibrinogen.…”
Section: Discussionsupporting
confidence: 85%
“…Bawadi et al 12) found that a low physical activity level and a poor diet were significantly associated with increased odds of periodontitis throughout conducting to determine the relationship between physical activity, healthy eating habits and periodontal health status among adults in Jordan. However, our findings showed that physical activity even divided into hard and mild physical activity and walking was no statistically significant difference in the prevalence of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional factors have been implicated in several chronic inflammatory diseases as risk factors included oral health such as periodontitis 10) . A few studies reported that there were more associations between nutrition and periodontitis as an inflammatory disease, including the effect of vitamin C, vitamin E, and carotenoids as dietary antioxidants in inflammation modulation 11) , and the impact of obesity on modulating the host's immune and inflammatory system leaving the patient with a greater risk of periodontitis 12) . Eating habits and nutrients also influence periodontitis, some studies also have reported that consumption of vitamin C, E and calcium is connected to periodontitis 13) .…”
mentioning
confidence: 99%
“…In addition, a lower level of physical exercise and the consumption of a poor diet were associated with increased odds of periodontal disease (12).…”
Section: Introductionmentioning
confidence: 98%